Continuous N-alkylation reactions of amino alcohols using γ-Al2O3 and supercritical CO2: unexpected formation of cyclic ureas and urethanes by reaction with CO2 - Streng, Emelia S.; Lee, Darren S.; George, Michael W.; Poliakoff, Martyn (Beilstein-Institut, 2017)
The use of γ-Al2O3 as a heterogeneous catalyst in scCO2, has be successfully applied to the amination of alcohols for the synthesis of N-alkylated heterocycles. The optimal reaction conditions (temperature and substrate flow rate) were determined using an automated self-optimising reactor, resulting in moderate to high yields of the target products. Carrying out the reaction in scCO2 was shown to be beneficial, as higher yields were obtained in the presence of CO2 than in its absence. A surprising discovery is that, in addition to cyclic amines, cyclic ureas and urethanes could be synthesised by incorporation of CO2 from the supercritical solvent into the product.